Educação para autonomia em kant e Adorno : formação cultural e semiformação - Canci, Zaira de Oliveira (2014)
The present research has a doublegoal. Investigating, first, how the majority concept of Kant is on the base of the adornian notion of education. Secondly, problematizing soon on what terms the autonomy notion assigned by Adorno to education, anchored on Kantian majority, is still appropriated to analyze the education commodification and, arising from it, the reductionism of cultural formation to vocational technical formation. This double goal is chased by three chapters. The first chapter, entitled origin and meaning of majority, addresses the legal and political dimensions of majority. It searches alerting the reader to the risks that emerge to the education field when the majority is reduced only to its legal sense. In other words, anchoring themselves in Kant's explanation, that the democratic and formative sense of education needs of the political conception of majority. Following, still in the first chapter, it treats of the modern origin of majority, pausing in the nexus between clarification and majority, in the way that appears on the Kant s text "Answer to question: what is clarification?". The second chapter concentrates on investigating, first, how the Kantian concept ok majority influences decisively on adornian concept of education as autonomy. Secondly, it treats of analyzing the critic sense of clarification assumed by Adorno, which drifts of a double movement of though: of its critic to the modern epistemological sense of clarification, which flows on the instrumentalization of reason taken by modern science; and, of its critic to reductionism of the cultural formation notion to semiformation. This double thought movement, and this is the most important conclusion of the chapter, is anchored by the Kantian nexus between the pedagogical clarification and majority. Lastly, thethird chapter treats, first, in abstract form of all developed rout in the dissertation, of the influence that the Kantian majority notion exerts in the Adorno sradio conferences. Following, with certain inspiration in the competent exegesis that Foucault does of the Kantian tex What is clarification? , we search for showing the present of the nexus between clarification and majority to treat about a contemporary educational issue of the first greatness, knowing, the cultural formation reductionism to vocational technical formation. The methodology that was used on three chapters of the dissertation is by a bibliography nature. Accordingly, all developed route on three chapters anchors on the hermeneutic procedure, which press the patience work of the text investigated listening and the effort of its rational reconstruction